Development, trade, and the WTO : a handbook - Hoekman, Bernard (World Bank WashingtonUS, 2002)
Places trade policy reform in a development context and discusses key dimensions of reform. Deals with the main aspects of the WTO and covers the areas that are the subject of WTO rules viz. trade in goods; trade in services; and, the protection of intellectual property. Discusses a number of regulatory issues. Focuses on specific process-related concerns of developing countries such as participation in the WTO; capacity building; and, implementation of WTO agreements. Summarizes a number of rules of thumb for good trade policy and reviews approaches to using the WTO (and regional agreements) as instruments for promoting development.